Integrated metabolomics and transcriptomics unravel the biosynthZaesis mechanism of anthocyanin in postharvest red raspberry (Rubus idaeus L.) - Sun, Huajun; Cui, Fangzheng; Liu, Ying; Qian, Lili; Zhu, Sijing; Li, Yue (Frontiers in Plant Science, 2025)
IntroductionAnthocyanins are crucial secondary metabolites that are responsible for pigment deposition in fruits. Raspberry fruit color shifts from white to red during natural or postharvest ripening. However, the precise mechanisms and biosynthetic pathways of anthocyanins in postharvest raspberries remain unclear.MethodsThis study used metabolomic and transcriptomic analyses to explore anthocyanin biosynthesis in postharvest raspberries at various color stages: white (RBT-1), white-to-pink (RBT-2), pink (RBT-3), red (RBT-4), and deep red (RBT-5).ResultsWe identified 43 key metabolites, and 13,239 DEGs linked to anthocyanin biosynthesis in postharvest raspberry colour development, including cyanidin-3-O-sophoroside and cyanidin-3-O-glucoside. The key DAMs in colored raspberries were gentiobioside, pelargonidin-3,5-O-diglucoside, cyanidin-3-O-sambubioside, and pelargonidin-3-O-sambubioside. Transcriptome analysis revealed 32 differentially expressed structural genes linked to anthocyanin and flavonoid synthesis, with significant upregulation of PAL, CHS, F3H, C4H, F3'H, DFR, ANS, CHI, and UFGT genes, which promote anthocyanin synthesis and pigment accumulation. Integrated analysis showed that cyanidin-3-O-sophoroside was correlated with 9 structural genes involved in anthocyanin biosynthesis, 19 transcription factors (TFs), and 14 hormone signaling-related genes.DiscussionThis study explored the regulatory mechanisms of MYB, WRKY, bHLH, and NAC transcription factors, as well as structural genes and phytohormone-related genes, in modulating anthocyanin metabolism during postharvest color changes in raspberries. The findings provide valuable insights for optimizing postharvest fruit storage conditions and enhancing fruit quality.